Journal of international law & international relations
The Journal of International Law and International Relations (JILIR) is a peer-reviewed scholarly journal that fosters interdisciplinary discourse at the nexus of international law and international relations. In promoting critical, informed, and interdisciplinary debate on international affairs, the JILIR provides a forum for the advancement of knowledge, ideas, dialogue and dialectic in both International Law and International Relations.